1999
DOI: 10.4269/ajtmh.1999.60.307
|View full text |Cite
|
Sign up to set email alerts
|

Mortality due to schistosomiasis mansoni: a field study in Sudan.

Abstract: Abstract. Although schistosomiasis affects 200 million persons, 20 million of whom have advanced disease, little is known about the mortality pattern in areas of endemic schistosomiasis mansoni. In an attempt to assess the mortality rates in an endemic area in Sudan, we conducted two demographic surveys in a village in the Gezira area. Clinical, sonographic, and parasitologic examinations were performed in a randomly selected sample of 25% of the population in 1987 and 1994. One of us asked each head of househ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 11 publications
(15 reference statements)
0
25
0
Order By: Relevance
“…Unlike in Ukerewe, studies carried out in other highly endemic African countries such as Egypt, the region of Gezira in Central Sudan and Albert Lake in Uganda showed significant changes of the liver and serious complications in adolescents (Doehring-Schwerdtfeger et al 1989;Kheir et al 1999;Kabatereine 2000). Various factors such as more frequently repeated re-infections, a higher cumulative worm load and genetic factors have been discussed to underly to these differences between endemic areas (Dessein et al 1999;Blanton et al 2005;Eboumbou et al 2005).…”
Section: Discussionmentioning
confidence: 88%
“…Unlike in Ukerewe, studies carried out in other highly endemic African countries such as Egypt, the region of Gezira in Central Sudan and Albert Lake in Uganda showed significant changes of the liver and serious complications in adolescents (Doehring-Schwerdtfeger et al 1989;Kheir et al 1999;Kabatereine 2000). Various factors such as more frequently repeated re-infections, a higher cumulative worm load and genetic factors have been discussed to underly to these differences between endemic areas (Dessein et al 1999;Blanton et al 2005;Eboumbou et al 2005).…”
Section: Discussionmentioning
confidence: 88%
“…In Sudan, a country endemic with schistosomiasis, AVH in the majority of cases is caused by portal hypertension due to schistosomal periportal fibrosis (PPF), while cirrhosis is less common[4]. Published data from Sudan showed that the crude mortality rate of schistosomiasis in a village in the Gezira state; an area endemic for schistosomiasis was 51/100000 per year with a case fatality per year of 1/1000 in those secreting eggs and 11/100 in those with bleeding varices[5]. Significant risk factors for variceal bleeding in patients with schistosomal portal hypertension, after at least one episode of bleeding compared to patients with schistosomal PPF without bleeding were splenic longitudinal dimension of more than 11 cm and PPF of ≥ grade III[6].…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate of schistosomiasis in published data from a village endemic with schistosomiasis in the Gezira state located in Sudan was 51/100,000 per year. The fatality rate per year is 1/1000 in patients secreting eggs and 11/100 in variceal bleeding patients [5] . Schistosoma mansoni (S.mansoni) complicated by portal hypertension has a major impact on morbidity and mortality because of esophagogastric variceal bleeding possibility [6] .…”
Section: Introductionmentioning
confidence: 99%